Radin mas folktales from singapore - Lee, olive (Funks & Wagnalls Inc. Singapore, 1988)
presents a critical examination of socialism as a response to contemporary societal and economic issues. The book delves into the flaws of capitalism and argues how socialism offers viable solutions to inequality, economic instability, and social injustice, proposing a roadmap for future societal progress.